2003
DOI: 10.1016/s0962-8924(02)00040-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging of signaling networks

Abstract: Receptor-triggered signaling processes exhibit complex cross-talk and feedback interactions, with many signaling proteins and second messengers acting locally within the cell. The flow of information in this inputoutput system can only be understood by tracking where and when local signaling activities are induced. Systematic strategies are therefore needed to measure the localization and translocation of all signaling proteins, and to develop fluorescent biosensors that can track local signaling activities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…Bovine brain extracts immunodepleted of Toca-1 were unable to support PtdIns(4,5)P 2 activation of N-WASP, and it was proposed that PtdIns(4,5)P 2 might regulate N-WASP activity through juxtapositioning of a regulator, such as a GEF (Ho et al, 2004). PtdIns(4,5)P 2 is primarily localized in the plasma membrane where it acts as a marker for actin assembly (Balla and Varnai, 2002;Huang et al, 2004;Meyer and Teruel, 2003), and recently it was demonstrated that N-WASP activation is ultrasensitive to small increases in PtdIns(4,5)P 2 density (Papayannopoulos et al, 2005). FRET analysis has described positioning of active N-WASP at membrane protrusions (Lorenz et al, 2004) and together these results suggest that N-WASP might function in mTuba-directed actin assembly through acute sensing of local membrane domains, marking a site for localized activation of Cdc42 by mTuba and subsequent regulation of Arp2/3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine brain extracts immunodepleted of Toca-1 were unable to support PtdIns(4,5)P 2 activation of N-WASP, and it was proposed that PtdIns(4,5)P 2 might regulate N-WASP activity through juxtapositioning of a regulator, such as a GEF (Ho et al, 2004). PtdIns(4,5)P 2 is primarily localized in the plasma membrane where it acts as a marker for actin assembly (Balla and Varnai, 2002;Huang et al, 2004;Meyer and Teruel, 2003), and recently it was demonstrated that N-WASP activation is ultrasensitive to small increases in PtdIns(4,5)P 2 density (Papayannopoulos et al, 2005). FRET analysis has described positioning of active N-WASP at membrane protrusions (Lorenz et al, 2004) and together these results suggest that N-WASP might function in mTuba-directed actin assembly through acute sensing of local membrane domains, marking a site for localized activation of Cdc42 by mTuba and subsequent regulation of Arp2/3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment took into account the spatial context of cellular signaling and only recently has spatial heterogeneity been seriously gaining momentum as a necessary dimension to consider in systems biology modeling and simulation. 12,[14][15][16] On a cellular systems scale, Lucchetta et al 27 used localized microfluidic flow to explore embryonic patterning compensation mechanisms against spatiotemporal perturbations applied to a Drosophila embryo. The robustness of the Drosophila patterning system to a large range of physicochemical parameters has been well-demonstrated using system-level mathematical models.…”
Section: Exploiting Microfluidic Flow For Unique Opportunities In Expmentioning
confidence: 99%
“…Correct interpretation of these signals is required for proper functioning of cells and organisms (Meyer & Teruel 2003). When a signalling cascade is modified, e.g.…”
Section: Introductionmentioning
confidence: 99%